Movement of Rehabilitated African Elephant Calves Following Soft Release Into a Wildlife Sanctuary - Goldenberg, Shifra Z.; Hahn, Nathan; Stacy-Dawes, Jenna; Chege, Stephen M.; Daballen, David; Douglas-Hamilton, Iain; Lendira, Reuben R.; Lengees, Meshack J.; Loidialo, Lemerketo Samuel; Omengo, Fred; Pope, Frank; Thouless, Chris; et al. (Frontiers in Conservation Science, 2021)
The ability to locate essential resources is a critical step for wildlife translocated into novel environments. Understanding this process of exploration is highly desirable for management that seeks to resettle wildlife, particularly as translocation projects tend to be expensive and have a high potential for failure. African savannah elephants (Loxodonta africana) are very mobile and rely on large areas especially in arid environments, and are translocated for differing management and conservation objectives. Thus, research into how translocated elephants use the landscape when released may both guide elephant managers and be useful for translocations of other species that adjust their movement to social and ecological conditions. In this study, we investigate the movement of eight GPS tracked calves (translocated in three cohorts) following their soft release into a 107 km2 fenced wildlife sanctuary in northern Kenya. We describe their exploration of the sanctuary, discovery of water points, and activity budgets during the first twenty-one, fourteen, and seven months after release. We compare these patterns to those of five wild elephants that were tracked and explore how patterns are affected by time since release, ecological conditions, and social factors. We find that calves visited new areas of the sanctuary and water points during greener periods and earlier post-release. Social context was associated with exploration, with later release and association with wild elephants predictive of visits to new areas. Wild elephants tended to use a greater number of sites per 14-day period than the released calves. Activity budgets determined from hidden Markov models suggested that released calves differed from wild elephants. The first two cohorts of calves spent a significantly greater proportion of time in the directed walk state and a significantly lower proportion of time in the encamped state relative to the wild elephants. Our results represent a step forward in describing the movements of elephant orphan calves released to the wild following a period of profound social disruption after losing their natal family and were rehabilitated under human care. We discuss the implications of the elephant behavior we observed for improving release procedures and for defining success benchmarks for translocation projects.